O2-S6.02 Occupational and intimate partner violence and inconsistent condom use with clients among female sex workers in southern India. (10th July 2011) - Deering, K; Bhattacharjee, P; Mohan, H L; Bradley, J; Shannon, K; Boily, M C; Ramesh, B M; Isac, S; Moses, S; Blanchard, J
Abstract : Background: Global reports suggest that interpersonal violence experienced by female sex workers (FSWs), including occupational violence (eg, by clients, CLViol) and intimate partner violence (IPViol) may be important structural determinants of vulnerability to HIV and sexually transmitted infections (STIs). This study characterised the type and frequency of CLViol and IPViol experienced by FSWs in southern India and examined the relationship between client violence and inconsistent condom use (ICU) with clients. Methods: Data were analysed from cross-sectional surveys of FSWs in three districts in Karnataka state (2007). ICU was defined as condom use frequency reported as 'never/sometimes/often' vs 'always', by repeat and occasional clients. CLViol and IPViol measures included having experienced physical violence in the past 6 months (ie, hurt, hit, kicked, punched, choked, burned) or sexual violence in the past year (ie, beaten or otherwise physically forced to have sexual intercourse). Results: Of our sample of 1245 FSWs, ICU was 13.0% with occasional and 20.2% with repeat clients. Overall, 13.1% of women reported physical violence from any perpetrator (CLViol: 5.5%; IPViol: 4.6%) and 9.7% reported sexual violence (CLViol: 5.2%; IPViol: 4.4%). In multivariable logistic regression analysis, the odds of ICU with occasional clients were significantly higher for women who had experienced physical CLViol (adjusted OR (AOR): 2.4, 95% CI: 1.2% to 4.8%) or sexual CLViol (AOR: 2.7, 95%CI: 1.3% to 5.5%). Similar results were found with repeat clients: AOR: 2.5, 95% CI: 1.4% to 4.6% and AOR 2.3, 95% CI: 1.3% to 4.2%, for physical and sexual violence respectively. A dose-response relationship between the number of times experiencing CLViol and increased ICU with both types of clients was also observed (p<0.001) (Abstract O2-S6.02 figure 1 ). IPViol was not significantly associated with ICU with clients. Experiencing CLViol was not associated with experiencing IPViol (p=0.321). Discussion: A strong independent relationship between experiencing client violence and inconsistent condom use with clients among FSWs in southern India was observed, highlighting FSWs' vulnerability to HIV/STI infection. Occupational violence against FSWs should be addressed within HIV/STI prevention programming. Structural-legal reforms to current sex work laws and safer-environment interventions should be developed to reduce violence and HIV/STI vulnerability among FSWs.